Upaya Peningkatan Pemasaran Produk Melalui Pendampingan Pembuatan Nama Produk, Kemasan dan Perizinan Usaha Dodol Desa Reksonegoro Kabupaten Gorontalo - Ibrahim, Melinda; Zainuddin, Muammar; Surusa, Frengky Eka Putra (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2019)
The main problems faced by dodol business doers at Reksonegoro in Gorontalo Regency can be seen in marketing management and financial management. In marketing management aspect,  it is found that there are some absences in cases of branding, packaging, Home-Industry Food Certification), and Halal certification issued by Institute for Food, Drug, and Cosmetics Studies - Indonesian Ulema Council.  In financial management aspect, it is indicated that there is a mixed financial management of both business and private needs with a very low discipline causing a financial misuse for private expenses.   The aim of this service activity is to improve the product competitiveness and business management of the residents at Reksonegoro in Gorontalo Regency.  The service programs are carried out through mentoring for a more informative, attractive branding and packaging, helping the issuance of Home-Industry Food Certification and Halal Certification by Institute for Food, Drug, and Cosmetics Studies - Indonesian Ulema Council, and assisting the financial management. The outputs succeeded in each program are a dodol?s branding and logo have been created, and two packaging designs for IDR 50.000,00, and IDR 100.000,00 have been made. Besides that, the partners in this activity have achieved some certifications namely Counseling Certificate, Home-Industry Food Certificate, and Halal certificate issued by  Institute for Food, Drug, and Cosmetics Studies - Indonesian Ulema Council of Gorontalo Province.  Through mentoring, the understanding of this business partners in the matter of financial management has significantly improved.